2010
DOI: 10.1038/hr.2010.112
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of a combination of Rho-kinase inhibitor and ACE inhibitor on tubulointerstitial fibrosis induced by unilateral ureteral obstruction

Abstract: We and others recently reported that long-term Rho-kinase inhibition has renoprotective effects. This study was designed to compare the effects of an angiotensin-converting enzyme (ACE) inhibitor (imidapril), a Rho-kinase inhibitor (fasudil) and a combination of them both on renal interstitial fibrosis induced by unilateral ureteral obstruction (UUO). We also attempted to elucidate the mechanism involved. Imidapril (50 mg l -1 ), fasudil (1 g l -1 ) or a combination of them both was given in drinking water to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 37 publications
(59 reference statements)
2
20
0
Order By: Relevance
“…Furthermore, many studies have shown that the RhoA/Rho-associated kinase pathway plays an important role in tissue fibrosis and that Rho-kinase inhibition prevents and ameliorates tissue fibrosis. 11,[20][21][22][23][24][25] Therefore, our results may raise the possibility of targeting the RhoA/ROCK pathway to prevent corporal fibrosis and preserve the corpus cavernosum in the early period after partial or incomplete nerve injury. One of the novel findings of this study was that the erectile response had not spontaneously normalized at 4 or 12 weeks after CN injury, despite recovery of Akt and eNOS phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, many studies have shown that the RhoA/Rho-associated kinase pathway plays an important role in tissue fibrosis and that Rho-kinase inhibition prevents and ameliorates tissue fibrosis. 11,[20][21][22][23][24][25] Therefore, our results may raise the possibility of targeting the RhoA/ROCK pathway to prevent corporal fibrosis and preserve the corpus cavernosum in the early period after partial or incomplete nerve injury. One of the novel findings of this study was that the erectile response had not spontaneously normalized at 4 or 12 weeks after CN injury, despite recovery of Akt and eNOS phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] Interstitial myofibroblast differentiation, macrophage infiltration, and podocyte injury: Immunohistochemical analysis in renal cortex using an antibody against anti-α-SMA, a marker of myofibroblast expression, anti-CD68, a macrophage marker, and anti-desmin, a marker of podocyte injury, was performed as reported previously. 8,9) Quantification of the α-SMA, CD68, and desmin-positive area was determined using a computeraided manipulator program as described previously. 8,9) In situ detection of renal superoxide anion generation: Superoxide anion generation in renal tissue of renal cortex was evaluated using the fluorescent dye dihydroethidium (DHE) as earlier reported.…”
Section: Renal Morphology and Glomerulosclerosis Injury Score (Gis)mentioning
confidence: 99%
“…The area of fibrotic lesions in the interstitium (fibrosis area) in renal cortex was determined on sections stained by Masson's trichrome method to stain collagen fibers (stained blue), using a computer-aided manipulator program as described previously. [7][8][9] Interstitial myofibroblast differentiation, macrophage infiltration, and podocyte injury: Immunohistochemical analysis in renal cortex using an antibody against anti-α-SMA, a marker of myofibroblast expression, anti-CD68, a macrophage marker, and anti-desmin, a marker of podocyte injury, was performed as reported previously. 8,9) Quantification of the α-SMA, CD68, and desmin-positive area was determined using a computeraided manipulator program as described previously.…”
Section: Renal Morphology and Glomerulosclerosis Injury Score (Gis)mentioning
confidence: 99%
“…9 ROCK has an important role in the differentiation of monocytes that mature into cardiac fibroblasts and induce fibrosis in murine ischemia/reperfusion injury. 10 In this issue of Hypertension Research, Takeda et al 11 describe a very elegant study that assessed for the first time the hypothesis that a combination of a ROCK inhibitor (fasudil) and an ACE inhibitor (imidapril) would improve renal interstitial fibrosis more than monotherapy, using an experimental model of normotensive renal fibrosis induced by unilateral ureteral obstruction (UUO). After surgery, mice were randomly assigned to imidapril, fasudil or a combination of the two for 11 days.…”
mentioning
confidence: 99%
“…11 By generating reactive oxygen species (ROS), NADPH oxidases contribute to oxidative stress and consequent cardiovascular and renal injury. ROS inuence diverse signal transduction pathways via oxidation of reactive cysteine residues on specic target molecules.…”
mentioning
confidence: 99%